CONTEXTUAL-BASED ENGLISH MODULE DEVELOPMENT TO IMPROVE SPEAKING SKILLS OF STUDENTS OF CLASS X SMA NEGERI 1 MUARA BELITI - syaprizal syaprizal; Agus Triyogo (LP4MK STKIP PGRI Lubuklinggau, 2021)
This study aims to 1) produce a contextual-based English learning module for high school students, 2) find out the improvement of students' speaking skills after using the developed English learning module. The research method used in this research is research and development using the ADDIE Analyze, Design, Develop, Implement, and Evaluate development model. The results of the validation of material experts 80.18, linguists 70.67, and media experts 89.72 were included in the very good category. The use of contextual-based English learning modules can improve students' speaking skills with the average acquisition score of students' speaking skills being 0.48.